EFEKTIFITAS SENAM DISMENORE TERHADAP PENANGANAN NYERI HAID PRIMER PADA REMAJA - Desti ' Ismarozi; Sri ' Utami; Riri Novayelinda ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract The dysmenorrhea exercise is an activities that can used for reducing of pain.  The aim of this research was to determinedthe effectiveness of dysmenorrhea exercise for recucing primary menstrual pain of adolescents. The design of this research is posttest only control group design. The groups were divided into experiment group and control group. The sample in the research is student of VIII class SMP Negeri 14 Pekanbaru. The total sample were 30 people who were taken by using purposive sampling techniques by noticing to the inclusion criteria. Measuring instruments that used in both groups are numeric rating scale for menstrual pain. Analysis used forunivariate distribution of age and menarche.The bivariateanalyzesused Mann Whitney test. The statistic test show the difference of experiment and control group with p-value 0,016 < α (0,05). It means that dysmenorrhea exercise was effectivefor reducing the primary menstrual pain. The result of this research is expected to be an alternative to reducing the pain of primary menstrual. Key words             : Dysmenorrhea exercise, handling, menstrual pain, numeric rating scale Bibliography:      : 47 (2001-2014)